A high-caloric diet rich in soy oil alleviates oxidative damage of skeletal muscles induced by dexamethasone in chickens. (1st January 2018) - Jiao, Hongchao; Zhou, Kaifeng; Zhao, Jingpeng; Wang, Xiaojuan; Lin, Hai
ABSTRACT: Objective: Glucocorticoids (GCs) can induce oxidative damage in skeletal muscles. The purpose of this study was to demonstrate a high caloric (HC) diet rich in soy oil would change the oxidative stress induced by a GC. Methods: The effect of dexamethasone (DEX) and HC diet on oxidative stress in plasma, skeletal muscles ( M. pectoralis major, PM; M. biceps femoris, BF), and mitochondria were determined. The biomarkers of oxidative damage and antioxidative enzyme activity were determined. The fatty acid profile of muscles and the activities of complex I and II in mitochondria were measured. Results: The results showed that DEX increased the concentrations of oxidative damage markers in plasma, muscles, and mitochondria. The activity of complex I was significantly suppressed by DEX. DEX-chickens had higher proportions of polyunsaturated fatty acids and lower proportions of monounsaturated fatty acids in the PM. A HC diet decreased the levels of oxidative damage biomarkers in plasma, muscles, and mitochondria. The interaction between DEX and diet suppressed the activities of complex I and II in HC-chickens. Discussion: Oxidative damage in skeletal muscles and mitochondria was the result of GC-induced suppression of the activity of mitochondrial complex I. A HC diet improved the antioxidative capacity and reduced the oxidative damage induced by the GC.